Bridget Jones the edge of reason - Davies, Andrew 1936-; Bevan, Tim; Fellner, Eric.; Cavendish, Jonathan; Kidron, Beeban; Curtis, Richard, 1956-; Brooks, Adam, 1956-; Zellweger, Renee, 1969-; Grant, Hugh.; Firth, Colin, 1960-; Broadbent, Jim.; Jones, Gemma; et al. (Universal City, CA : Universal, 2005)
London-based thirty-something Bridget Jones continues her romantic relationship with Mark Darcy, despite many humorous complications.
Special features: Anamorphic widescreen -- Alternate beginning -- Deletec scenes -- "Who's your man?" quiz -- Look inside "The Big Fight" -- Discussing with Renee Zellweger and Colin Firth -- Interview from serious journalist Bridget Jones and actor Colin Firth -- Language: English Dolby digital 5.1 ; Spanish Dolby digital 5.1 ; French Dolby digital 5.1 -- Subtitles: English, Spanish, French.
Based on the novel: Bridget Jones, the edge of reason / by Helen Fielding.
Originally produced as a motion picture in 2004.
Special features (28 min.): optional audio commentary by Kidron; "The big fight" featurette (5 min.); "Who's your man?" interactive quiz; 3 deleted scenes with introductions (10 min. total); "Mark and Bridget : forever?" featurette (5 min.); "Bridget Jones interviews Colin Firth" (5 min.); "Lonely London" featurette (3 min.); 15 cast & filmmaker bios.
Director of photography, Adrian Biddle ; editor, Greg Hayden ; music by Harry Gregson-Williams.
Renee Zellweger, Hugh Grant, Colin Firth, Jim Broadbent, Gemma Jones, Jacinda Barrett, James Callis, Shirley Henderson, Sally Phillips, Neil Pearson, Jessica Stevenson.
MPAA rating: R; for language and some sexual content.
Keywords: Fielding, Helen, -- 1958- -- Film adaptations; Jones, Bridget -- (Fictitious character) -- Drama; Single women -- Drama; Man-woman relationships -- Drama; Jones, Bridget (Personaje literario); Relaciones hombre-mujer; French language materials; Spanish language materials; London (England) -- Drama; Film sequels; Feature films -- Great Britain; Feature films -- France; Romance films; Romantic comedy films; Video recordings for the hearing impaired